Isolation of Lytic and Lysogenic Bacteriophages Specific to Pseudomonas spp - Doshi, Dhruvi M; Bhanderi, Bharat B (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
In the present study, total 12 Pseudomonas spp. were obtained from 94 dogs suffering from otitis externa, and were characterized  and subjected to in vitro antibiotic susceptibility test using commonly used antimicrobial drugs. Virulence associated gene algD (alginate synthesis) was detected in 91.67% isolates of Pseudomonas spp. Out of 12 Pseudomonas spp. isolates, six were selected and  subjected for the isolation of bacteriophages. Total 12 samples, i.e., eight sewage water and four pond water samples were processed  for isolation of the bacteriophages specific to six Pseudomonas spp. selected using double agar overlay assay, out of which 50.00%  (6/12) samples showed presence of phages in the form of plaque. Out of six samples three each were lytic and lysogenic phages. The  bacteriophages were screened for the presence of integron genes (intI1, intI2 and intI3) where intI1 and intI2 were detected in two  lysogenic phages each. Out of three lysogenic phages, one was responsible for conversion of phenotypically non-mucoid strain of  Pseudomonas spp. to mucoid. Moreover, a comparative in vitro antibiotic susceptibility zone analysis of the wild Pseudomonas spp.  vs. lysogenic phage affected Pseudomonas spp. revealed that lysogenic phage infection altered the antimicrobial susceptibility of  lysogenic phage affected Pseudomonas spp. isolates at a sub-inhibitory concentration of antibiotics, suggesting that they might be  precursory to antimicrobial resistance.
Keywords: Antibiotic resistance; Integron genes; Lytic and Lysogenic bacteriophages; Mucoid variation